Manajemen Media Pembelajaran Berbasis Chromebook dalam Meningkatkan Kualitas Belajar Siswa Kelas V - R Supyan Sauri; Ridwan Asyadi; Aziza, Nisa Panca; Vita Puspita Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This research aims to analyze the use of Chromebooks in improving the learning quality of fifth grade students at SDN Cangkuang 02, Bandung Regency, using the POAC (Planning, Organizing, Actuating, Controlling) management approach. This research is motivated by the need to apply technology in learning to support 21st century skills, such as digital literacy, collaboration and creativity. The research method used is descriptive qualitative, with data collection techniques through interviews, observation and document analysis. The research results show that the implementation of Chromebooks in learning is carefully planned, including providing devices, teacher training, as well as managing time and technology-based teaching materials. Organizing the program involved collaboration between principals, teachers, students, and IT technicians to ensure effective use of Chromebooks. The implementation of Chromebook-based learning has succeeded in increasing student participation through more interactive and collaborative learning. Control is carried out through regular evaluation of Chromebook use, both from a technical perspective and student learning outcomes. The obstacles faced, such as unstable internet connections and limited student understanding, were overcome through infrastructure improvements and additional training. Overall, the use of Chromebooks with the POAC management approach has been proven to be able to improve the quality of student learning, marked by increased learning motivation, understanding of the material, and students' digital skills.